Step towards monitoring intelligent agents in healthcare information systems - Sousa, Regina (2020)
A platform for establishing interoperability between heterogeneous information systems implemented in a hospital environment is more a requirement than an option. The Agency for the Integration, Diffusion and Archiving of Medical and Clinical Information (AIDA) is an interoperability platform designed specifically to address the problem of integrating information from multiple systems and addressing interoperability, confidentiality, integrity and data availability. This article focuses on the relevance and need for such vigilance, finding and designing effective new ways to establish them. This study culminated in the creation of AIDAMonit, a surveillance platform developed and tested by ALGORITMI Center researchers, which has shown promise and is extremely beneficial for the well-functioning of the health facilities currently using the AIDA platform.